Aryl hydrocarbon receptor-mediated disruption of contact inhibition is associated with connexin43 downregulation and inhibition of gap junctional intercellular communication - Andrysík, Zdeněk; Procházková, Jiřina; Kabátková, Markéta; Umannová, Lenka; Simečková, Pavlína; Kohoutek, Jiří; Kozubík, Alois; Machala, Miroslav; Vondráček, Jan (Archives of toxicology, 2013)
The aryl hydrocarbon receptor (AhR) contributes to the control of cell-to-cell communication, cell adhesion, migration or proliferation. In the present study, we investigated the regulation of connexin43 (Cx43) and Cx43-mediated gap junctional intercellular communication (GJIC) during the AhR-dependent disruption of contact inhibition in non-tumorigenic liver epithelial cells. The contact inhibition of cell proliferation is a process restricting the cell division of confluent non-transformed cells, which is frequently abolished in cancer cells; however, the mechanisms contributing to its disruption are still only partially understood. Disruption of contact inhibition, which was induced by toxic AhR ligands 2,3,7,8-tetrachlorodibenzo-p-dioxin (TCDD) or polycyclic aromatic hydrocarbons in epithelial WB-F344 cells, reduced Cx43 protein levels, possibly via enhanced proteasomal degradation, significantly decreased the amount of gap junction plaques and downregulated GJIC, in an AhR-dependent manner. Although both intracellular and membrane Cx43 pools were markedly reduced in cells released from contact inhibition by TCDD, siRNA-mediated Cx43 knock-down was not sufficient to stimulate proliferation in contact-inhibited cells. Our data suggest that downregulation of Cx43/GJIC in non-transformed epithelial cells is an inherent part of disruption of contact inhibition, which occurs at the post-transcriptional level. This process runs in parallel with alterations of other forms of cell-to-cell communication, thus suggesting that toxic AhR agonists may simultaneously abrogate contact inhibition and reduce GJIC, two essential mechanisms linked to deregulation of cell-to-cell communication during tumor promotion and progression.
Keywords: kontaktní inhibice; RNA Interference; Gene Knockdown Techniques; Proteasome Endopeptidase Complex; Animals; Connexin 43; konexin 43; Ligands; Indoles; benz(a)anthraceny; Rats; buněčné linie; Gap Junctions; mezerový spoj; transfekce; ligandy; Signal Transduction; fosforylace; mezibuněčná komunikace; polychlorované dibenzodioxiny; časové faktory; Benz(a)Anthracenes; Cell Line; RNA interference; karcinogeny; Dose-Response Relationship, Drug; fluoreny; proliferace buněk; játra; Transfection; down regulace; epitelové buňky; floroglucinol; Epithelial Cells; nádorová transformace buněk; receptory aromatických uhlovodíků; Liver; zvířata; Down-Regulation; Phosphorylation; Time Factors; indoly; Receptors, Aryl Hydrocarbon; genový knockdown; Liver Neoplasms; signální transdukce; vztah mezi dávkou a účinkem léčiva; Cell Transformation, Neoplastic; proteasomový endopeptidasový komplex; Contact Inhibition; nádory jater; krysa rodu Rattus; Fluorenes; Cell Proliferation; Carcinogens; Polychlorinated Dibenzodioxins; Phloroglucinol; Cell Communication